Circular motion of multiple nonholonomic robots under switching topology with ordinal ranking. Issue 15 (October 2020) - Chen, Guoyong; Fu, Weiming; Kang, Yu; Qin, Jiahu; Zheng, Wei Xing
Abstract: This paper investigates the circular motion of a group of n ( n  ≥ 2) nonholonomic robots over time-varying communication networks. We aim to achieve a balanced circular motion centered at a location determined by each robot under the assumption that the global ranking of any robot is unknown. A back-stepping based controller is firstly designed to make all the robots rotate around a common center, the position of which is obtained through executing a consensus algorithm by each robot. Then, the maximum and minimum consensus algorithm and a distributed modified ordinal ranking algorithm are applied to set the rotation radius, angular velocity, and orientation parameters in a distributed manner such that all the robots can uniformly space on the common circle. At last, the effectiveness of the proposed algorithms is illustrated through a simulation example.